Wound healing properties of a new formulated flavonoid-rich fraction from Dodonaea viscosa Jacq. leaves extract - Subramanian, Shanthi; Duraipandian, Chamundeeswari; Alsayari, Abdulrhman; Ramachawolran, Gobinath; Wong, Ling Shing; Sekar, Mahendran; Gan, Siew Hua; Subramaniyan, Vetriselvan; Seethalakshmi, S; Jeyabalan, Srikanth; Dhanasekaran, Sivaraman; Chinni, Suresh V.; et al. (Frontiers in Pharmacology, 2023)
Dodonaea viscosa Jacq. (D. viscosa) belongs to the family of Sapindaceae, commonly known as “Sinatha”, is used as a traditional medicine for treating wounds due to its high flavonoids content. However, to date there is no experimental evidence on its flavonoid-rich fraction of D. viscosa formulation as an agent for healing wounds. The present study is aimed at evaluating the wound healing effect of ethyl acetate fraction of D. viscosa leaves on dermal wounds. The ethyl acetate fraction was produced from a water-ethanol extract of D. viscosa leaves and was quantitatively evaluated using the HPLC technique. The in-vivo wound healing ability of the ethyl acetate fraction of D. viscosa ointment (DVFO) 2.5%w/w and 5%w/w) was investigated in Sprague-Dawley rats utilizing an incision and excision paradigm with povidone-iodine ointment (5% w/w) as a control. The percentage of wound closure, hydroxyproline and hexosamine concentrations, tensile strength and epithelialization duration were measured. Subsequently, histopathology analysis of skin samples as well as western blots were performed for collagen type 3 (COL3A1), basic fibroblast growth factor (bFGF) and vascular endothelial growth factor (VEGF). The ethyl acetate fraction of D. viscosa revealed flavonoids with high concentrations of quercetin (6.46% w/w) and kaempferol (0.132% w/w). Compared to the control group, the DVFO (2.5% and 5.0% w/w) significantly accelerated wound healing in both models, as demonstrated by quicker wound contraction, epithelialization, elevated hydroxyproline levels and increased tensile strength. Histopathological investigations also revealed that DVFO treatment improved wound healing by re-epithelialization, collagen formation and vascularization of damaged skin samples. Western blot analysis further demonstrated an up-regulation of COL3A, VEGF and bFGF protein in wound granulation tissue of the DVFO-treated group (p<0.01). It is concluded that flavonoid-rich D. viscosa ethyl acetate fraction promotes wound healing by up-regulating the expressions of COL3A, VEGF and bFGF protein in wound granulation tissue. However, extensive clinical and pre-clinical research on the flavonoid-rich fraction is needed to determine its significant impact in the healing of human wounds.